Solid State Composites and Hybrid Systems : Fundamentals and Applications - Savkina, Rada; Khomenkova, Larysa; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Solid state composites and hybrid systems offer multifunctional applications in various fields of human life, demonstrating solutions to the key problems of the environment, human health, biology, medicine, electronics, energy harvesting and storage. Exploring this innovative field of research, this book details the wide range of materials, techniques, and approaches utilised in composite and hybrid structures in recent years. It will be of interest not only for experienced researchers but also for postgraduate students and young researchers entering the fields of nanoscience, material sciences, and bioengineering.Features: Contains the latest research developments in the materials, techniques, patents, and approaches in the fieldIncludes both fundamental aspects and applied researchEdited by two highly experienced researchersAccompanied and complimented by electronic supplementary resources.
Chapter 1: Solid State Nanocomposites and Hybrid Systems: General Remarks -- --Larysa Khomenkova and Rada Savkina -- Chapter 2: Multifunctional Zirconia-based Nanocomposites -- --Nadiia Korsunska and Larysa Khomenkova -- Chapter 3: Semiconductor Nanocrystals Embedded in Polymer Matrix -- --Lyudmyla Borkovska -- Chapter 4: Development of Multifunctional Nanocomposites by Cavitation -- --Rada Savkina -- Chapter 5: Solid State Composites Produced by Ion Beam Processing -- --Aleksej Smirnov -- Chapter 6: Solid State Composites and Multilayers Produced by Magnetron Sputtering -- --Larysa Khomenkova and Nadiia Korsunska.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Material Science; SCIENCE / Chemistry / Industrial & Technical; Composite structure fabrication; Hybrid structures; Microelectronics; Multiferroic hybrid structure; Nanoelectronics; Solid state composites; Composite materials; Polymeric composites; Nanocomposites (Materials); Electronic books